The Library Consortium of New Zealand's Shared IRR Infrastructure - Murdoch, Craig; Schweer, Andrea; Brown, Allison; Lockett, Andrew; Miller, Kate (Open Repositories, 2012)
The Library Consortium of New Zealand has run an Institutional Research Repository Project for three universities and one institute of technology in New Zealand since 2006. After a brief introduction to the context in which the project operates, this document describes the Institutional Research Repositories that are part of this project and their shared infrastructure. Particular emphasis is placed on advantages and challenges created by the shared infrastructure.